A minireview on the bioremediative potential of microbial enzymes as solution to emerging microplastic pollution - De Jesus, Rener; Alkendi, Ruwaya (Frontiers in Microbiology, 2023)
Accumulating plastics in the biosphere implicates adverse effects, raising serious concern among scientists worldwide. Plastic waste in nature disintegrates into microplastics. Because of their minute appearance, at a scale of < 5 mm, microplastics easily penetrate different pristine water bodies and terrestrial niches, posing detrimental effects on flora and fauna. The potential bioremediative application of microbial enzymes is a sustainable solution for the degradation of microplastics. Studies have reported a plethora of bacterial and fungal species that can degrade synthetic plastics by excreting plastic-degrading enzymes. Identified microbial enzymes, such as IsPETase and IsMHETase from Ideonella sakaiensis 201-F6 and Thermobifida fusca cutinase (Tfc), are able to depolymerize plastic polymer chains producing ecologically harmless molecules like carbon dioxide and water. However, thermal stability and pH sensitivity are among the biochemical limitations of the plastic-degrading enzymes that affect their overall catalytic activities. The application of biotechnological approaches improves enzyme action and production. Protein-based engineering yields enzyme variants with higher enzymatic activity and temperature-stable properties, while site-directed mutagenesis using the E. coli model system expresses mutant thermostable enzymes. Furthermore, microalgal chassis is a promising model system for “green” microplastic biodegradation. Hence, the bioremediative properties of microbial enzymes are genuinely encouraging for the biodegradation of synthetic microplastic polymers.